2020
DOI: 10.31557/apjcc.2020.5.4.265-271
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness and Attitude on Cervical Cancer Prevention among Female Preparatory Students in Ziway town, Oromia Regional State, Ethiopia

Abstract: Objective: Cervical cancer is common disease worldwide and ranks fourth among all malignancies for women. It has been reported to have been responsible for almost quarter of a million deaths annually, of which about 85% occurred in developing nations. Hence, the present study was conducted to assess the knowledge and attitude on cervical cancer prevention and its associated factors among female students in Batu Preparatory School, Ziway town, Oromia Regional State, Ethiopia in 2018. Methods: Institution based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
4
1
Order By: Relevance
“…It is to be noted that there were region-wide differences observed in the present study regarding the correct knowledge about risk factors and symptoms where women from Delhi (64.9% and 54.2%) were found to have better knowledge than women from Rohtak (30% and 37.7%) for both risk factors and symptoms, respectively. The figures from Delhi are in accordance with other studies (Mengesha et al, 2020;Owoeye and Ibrahim, 2013), while those from Rohtak reveal a poorer picture where the awareness is considerably lower than the studies from other lower-middle income countries (Kifle et al, 2020;Simo et al, 2021) (Mengesha et al, 2020) (Hoque and Hoque, 2009). The figures from Delhi are similar to a study from Ghana (Ebu et al, 2015) where 30.6% of the participants had heard about cervical cancer.…”
Section: Discussionsupporting
confidence: 85%
“…It is to be noted that there were region-wide differences observed in the present study regarding the correct knowledge about risk factors and symptoms where women from Delhi (64.9% and 54.2%) were found to have better knowledge than women from Rohtak (30% and 37.7%) for both risk factors and symptoms, respectively. The figures from Delhi are in accordance with other studies (Mengesha et al, 2020;Owoeye and Ibrahim, 2013), while those from Rohtak reveal a poorer picture where the awareness is considerably lower than the studies from other lower-middle income countries (Kifle et al, 2020;Simo et al, 2021) (Mengesha et al, 2020) (Hoque and Hoque, 2009). The figures from Delhi are similar to a study from Ghana (Ebu et al, 2015) where 30.6% of the participants had heard about cervical cancer.…”
Section: Discussionsupporting
confidence: 85%
“…Brazil has the highest HNSCC incidence rate among South American countries, with an estimated risk of 10.69 new cases per 100,000 men and 3.71 per 100,000 women, the fifth and 13 th most frequent causes of neoplasm, among all cancers respectively (Sung et al, 2021). To understand university students' knowledge of HPV and its relationship with HNSCC, especially oral cancer, we found data indicating that students had gaps in their knowledge of the viral relationship with these neoplasms, a fact already observed in other studies (Luz et al, 2014;Silva et al, 2017aSilva et al, , 2017bBurlamaqui et al, 2017;Costa et al, 2017;Kifle et al, 2020;Saleemet al, 2021). Some studies have shown university students' poor knowledge on the relation virus which causes genital warts in both men and women positively influenced knowledge of the viral relationship and the emergence of HNSCCs including oral cancer.…”
Section: Discussionsupporting
confidence: 52%
“…The majority of the respondents were businesswomen who probably leave their homes early for their business only to come back in the evening and may never have the opportunity of hearing about this disease except if it is brought down to churches or in meetings. This evidence is further strengthened by the result of a regional study in Ethiopia which reported that only 21% of the participants had good knowledge of cervical cancer prevention (Kifle et al, 2020). In a qualitative study on awareness, perception, and factors affecting utilization of cervical cancer screening services among women in Ibadan, the subjects verbalized that teachings on cervical cancer are not integrated into the routine talks at the hospital (Urasa, and Djay, 2011).…”
Section: Discussionmentioning
confidence: 99%